Will Africa Be Able to Keep Its Promises to Reduce Greenhouse Gases? A Review of African Countries’ Commitments at COP 21 - (:unkn) unknown (My University, 2018)
This study describes the different types of commitments made by Africans in their National Determined Contributions (NDCs) and tries to explain whether or not it will be possible for them to fulfill their commitments. For this purpose, we operate all African NDCs formally presented at COP 21 in Paris in 2015 in which the greenhouse gas (GHG) reduction commitments are presented. The analysis reveals three types of commitments-namely, conditional commitments, not conditional on international aid, and both at the same time. Countries with conditional commitments subject to external financing are likely to fulfill their commitments that are stronger. Only countries with unconditioned commitments are more realistic not relying on external assistance that is becoming more and more hypothetical. Beyond the types of commitments, other types of obstacles such as the blurred legal form of the Paris Agreement and the preference for Adaptation could make it difficult to fulfill the commitments of African countries.
Keywords: African Research